2009
DOI: 10.1021/jm900611t
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design, Synthesis, and Biological Evaluation of a Series of Novel and Reversible Inhibitors for the Severe Acute Respiratory Syndrome−Coronavirus Papain-Like Protease

Abstract: We describe here the design, synthesis, molecular modeling, and biological evaluation of a series of small molecule, nonpeptide inhibitors of SARS-CoV PLpro. Our initial lead compound was identified via high-throughput screening of a diverse chemical library. We subsequently carried out structure-activity relationship studies, and optimized the lead structure to potent inhibitors that have shown antiviral activity against SARS-CoV infected Vero E6 cells. Based upon the X-ray crystal structure of one of the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 30 publications
3
153
0
2
Order By: Relevance
“…2729, 34 Four inhibitor structures from these two scaffolds are shown in Supplementary Figure S2, with I-1 and I-2 representing scaffold 1, and I-3 and I-4 representing scaffold 2. Inhibitors I-2 and I-3 exhibited excellent inhibitory activities with IC 50 values of 0.34 µM and 0.6 µM against SARS-PLpro, with SARS antiviral activities of 2 µM and 15 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2729, 34 Four inhibitor structures from these two scaffolds are shown in Supplementary Figure S2, with I-1 and I-2 representing scaffold 1, and I-3 and I-4 representing scaffold 2. Inhibitors I-2 and I-3 exhibited excellent inhibitory activities with IC 50 values of 0.34 µM and 0.6 µM against SARS-PLpro, with SARS antiviral activities of 2 µM and 15 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors I-2 and I-3 exhibited excellent inhibitory activities with IC 50 values of 0.34 µM and 0.6 µM against SARS-PLpro, with SARS antiviral activities of 2 µM and 15 µM, respectively. 27, 34 Two SARS-PLpro complex crystal structures, with lead inhibitors from each scaffold ( I-2 or I-3 ) revealed that inhibitors bind not to the catalytic site of the PLpro enzyme, but to the BL2 loop, blocking the entrance of the active site. This appears to prevent substrate access to the catalytic site, inhibiting PLpro enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…12,13) Fewer inhibitors of PL pro have been studied, and those that have been studied include thiopurine analogs and benzamide derivatives. 14,15) No naturally derived inhibitor of this protease has been reported previously. In the study described in this letter, an intensive hunt for effective anti-SARS drug was undertaken by screening natural products for inhibitory activity against SARS-CoV PL pro .…”
Section: Diarylheptanoids From Alnus Japonica Inhibit Papain-like Promentioning
confidence: 99%
“…Membran füzyon inhibitörlerinin de virüslerin hücre içerisine girişini engelleyebileceği düşünülmektedir (62,124). Viral S proteinine karşı geliştirilen antikorlar da coronavirüslerin hücre içerisine girişini durdurmaktadır (41,125). Domuz ve tavuk coronavirüslerine karşı geliştirilen bazı aşılar mevcuttur.…”
Section: Coronavirüslerin Patogenezi Ve Bağışıklıkunclassified